Implementasi Pembelajaran Drill and Practice dengan Proyek Untuk Meningkatkan Hasil Capaian Belajar Mahasiswa - Masjudin, Masjudin; Sukarma, I Ketut; Sabrun, Sabrun (Media Pendidikan Matematika, 2022)
The learning of introductory mathematics courses in the Undikma FSTT Mathematics Education Study program has so far been carried out in a monotonous manner. The lecturer explains the material, gives examples of questions, and gives exercises. The impact is the low achievement of student learning outcomes. Therefore, the purpose of this research is to improve student learning outcomes through the application of drill and practice learning with projects. This type of research is classroom action research. Data collection was carried out by evaluating student learning outcomes. The results of the study obtained an average score of student learning outcomes reaching 89.2% in the Very Good category. Thus, it can be concluded that the Implementation of Drill and Practice Learning with Projects able to Improve Student Learning Outcomes